Eksplorasi dan Digitalisasi Manuskrip Keagamaan: Pengalaman di Minangkabau - Ridwan Bustamam (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
Islamic Manuscript of Nusantara has long been the object of research. Center for Research and Development of Religious Literature and Heritage Office for Research and Development and Training began to seriously conserve the manuscript systematically since 2008 until now, among others through the digitalization of religious classical manuscripts. Until 2016, about 2,203 titles of religious manuscripts were successfully digitized from various parts of Indonesia, including the religious manuscripts of West Sumatra. Digitalization activities in this area are not as easy as planned, many obstacles to be faced by the digital team, technical issues and obstacles that arise from the owner of the script itself. The implementation strategy of digitizing manuscript used such as involving manuscripts from MANASSA, SULUAH Padang, IAIN Imam Bonjol Padang, and Andalas Padang University. In fact, there are still many religious manuscripts in West Sumatera that have not been photographed until 2016. Due to limited quotas, the manuscripts that are digitized are only 45 manuscripts, coming from three regions: 1) Pauh Kambar Hilir, Nan Sabaris, Padang Pariaman; 2) Batu Baraia, Saturday Feed, Luhak, Fifty Koto; 3) Kasiak, Koto Sani, Sumani, Solok. This community-owned manuscript contains among others tauhid, tafseer, fiqh, mujarabat, falakiyah, nahwu-naraf knowledge, and tasawuf. One of the most important recommendations of the digitalization team is: